2015
DOI: 10.5455/ijmsph.2015.0808201415
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight in schoolgoing adolescents of Surat city, Gujarat, India

Abstract: Background: The prevalence of obesity is increasing with the changing lifestyle of families over the past few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…In Pune, in Western India, the prevalence of overweight in children in the age group 9-16 years was 27.5% for boys and 20.9% for girls [26]. In Surat, the prevalence of overweight and obesity in boys was 12.4 and 8.2%, respectively, and in girls it was 7.2 and 2.7%, respectively [18]. Kapil et al reported the prevalence of obesity in children aged 10-16 years in Delhi to be 8.0% for boys and 6.0% for girls [27].…”
Section: Gendermentioning
confidence: 97%
See 1 more Smart Citation
“…In Pune, in Western India, the prevalence of overweight in children in the age group 9-16 years was 27.5% for boys and 20.9% for girls [26]. In Surat, the prevalence of overweight and obesity in boys was 12.4 and 8.2%, respectively, and in girls it was 7.2 and 2.7%, respectively [18]. Kapil et al reported the prevalence of obesity in children aged 10-16 years in Delhi to be 8.0% for boys and 6.0% for girls [27].…”
Section: Gendermentioning
confidence: 97%
“…Another study from Central India found 3.1% (95% CI 2.5-3.8) of children between 10 and 17 years to be overweight and 1.2% (95% CI 0.8-1.8) to be obese and overall 4.3% were overweight/obese [17]. From Surat, in Western India, Gamit et al reported the prevalence of overweight and obesity to be 10.2 and 6%, respectively [18]. In Kanpur, the prevalence of overweight and obesity were 4 and 2%, respectively.…”
Section: Indian Prevalencementioning
confidence: 99%
“…[10][11][12] However, studies conducted by Anuradha et al, Nawab et al, and Jain et al reported comparatively higher prevalence ranging from 9.8% to 23.8% and 4.8% to 8.4%, respectively. [13][14][15] In contradiction to that, Vohra et al reported comparatively lower prevalence (4.17% and 0.27%, respectively).…”
Section: Internationalmentioning
confidence: 99%
“…Similar findings were also reported in earlier studies too. [10,11,14,17,20,21] Even a nationwide survey report by the National Institute of Nutrition, India, revealed the prevalence of overweight and obesity significantly higher among adolescent of higher socioeconomic status. [22] This could be attributed to the fact that those belonging to affluent group have more purchasing power and therefore are more habitual toward intake of food items from outside in the form of snacks, junk food, street dishes, etc., having high content of trans-fatty acids.…”
Section: Internationalmentioning
confidence: 99%
See 1 more Smart Citation